2015
DOI: 10.4269/ajtmh.15-0113
|View full text |Cite
|
Sign up to set email alerts
|

Strong Association Between Human and Animal Brucella Seropositivity in a Linked Study in Kenya, 2012–2013

Abstract: Brucellosis is a common bacterial zoonotic infection but data on the prevalence among humans and animals is limited in Kenya. A cross-sectional survey was conducted in three counties practicing different livestock production systems to simultaneously assess the seroprevalence of, and risk factors for brucellosis among humans and their livestock (cattle, sheep, camels, and goats). A two-stage cluster sampling method with random selection of sublocations and households was conducted. Blood samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
132
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(164 citation statements)
references
References 31 publications
23
132
9
Order By: Relevance
“…from animals to humans in the former than in the latter. Similarly, in predominantly pastoral communities of Kenya, a high prevalence of brucellosis seropositivity in humans and livestock, a two to four fold higher prevalence in humans than in animals, and a strong household level association of seropositivity in humans and animals have been described [117]. In rural Ethiopia, livestock delivery is often assisted with bare hands and consuming raw milk is a common practice in a significant segment of the population.…”
Section: Resultsmentioning
confidence: 99%
“…from animals to humans in the former than in the latter. Similarly, in predominantly pastoral communities of Kenya, a high prevalence of brucellosis seropositivity in humans and livestock, a two to four fold higher prevalence in humans than in animals, and a strong household level association of seropositivity in humans and animals have been described [117]. In rural Ethiopia, livestock delivery is often assisted with bare hands and consuming raw milk is a common practice in a significant segment of the population.…”
Section: Resultsmentioning
confidence: 99%
“…About 4.96% prevalence of brucellosis has been reported among PUO and occupationally exposed individuals in Goa [18], 24.5% in Ludhiana, India [19]. Globally several studies showed the similar seroprevalence such as 6.4% in Iran [20], 5.2% in Afghanistan [21], 3.4% in Central Anatolia [22], 19% in Saudi Arabia [23], 53.25% in Mongolia [24], 20.5% in Tanzania [25], 6.26% in Egypt [26], 16% in Kenya [27], 2.15% in Ethiopia [28], 24.1% in abbatoir workers of Abuja [29], 17% in Uganda [30] and 3.8% in Chad [31].…”
Section: Discussionmentioning
confidence: 80%
“…Our search identified one study that used random sampling procedures in linked human and animal livestock populations [32]. …”
Section: Discussionmentioning
confidence: 99%